Peran Alumni Dalam Pemasaran Jasa Pendidikan Di Pondok Pesantren Darul Mukhlishin Panggung Sampang - Munib, Munib; Khotimah, Khusnul (AL -ALLAM, 2023)
In the current era of globalization, in the world of education there is competition between one institution and another. So the role of alumni here has a strong influence in marketing education services at the Darul Mukhlishin Islamic Boarding School. Based on this, there are two research focuses that are the main studies in this study, namely: First, what activities involve alumni in Darul Mukhlishin Islamic Boarding School activities?, Second, how are alumni involved by educational institutions in marketing educational services at Pondok Pesantren? Darul Mukhlishin Islamic Boarding School?. This research method uses a descriptive qualitative approach and type of field research. The sources of data obtained are through interviews, observation and documentation. The informants are the Head of Pondok, Alumni Management and the Community. The results of the study show that: First, Darul Mukhlishin Islamic Boarding School involves alumni in marketing educational services, namely with a marketing concept, namely promotion through social media (Whastaap, Facebook, and Youtobe), as well as introducing by holding activities. This concept is in accordance with the 7P Marketing mix Concept.15 Promotion can also be done through the involvement of alumni who always promote to the community. Second, the impact of the alumni's role in marketing educational services to cottages is the increase in Pondok facilities, the assistance in managing new programs and the increasing interest of prospective new students. Alumni have a strong influence on public trust aboutthe Pondok this is in accordance with the opinion of Fitria Halim and Ahmad Husein Ritongga Strengthening the Company's brand